2015
DOI: 10.1155/2015/817134
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Homogeneous Pilus Structure from Monomeric Data and Sparse Constraints

Abstract: Type IV pili (T4P) and T2SS (Type II Secretion System) pseudopili are filaments extending beyond microbial surfaces, comprising homologous subunits called “pilins.” In this paper, we presented a new approach to predict pseudo atomic models of pili combining ambiguous symmetric constraints with sparse distance information obtained from experiments and based neither on electronic microscope (EM) maps nor on accurate a priori symmetric details. The approach was validated by the reconstruction of the gonococcal (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Thus, the specific amino acid sequences and structures of monomers will clearly influence the assembly of a pilus and its functions (Vargas et al, 2013; Xiao et al, 2015). Previous researches have suggested that the length of the amino acid sequence and the conformation of G. sulfurreducens pilins leads to a compact assembly mode that may account for the electrical conductivity (Malvankar et al, 2011; Xiao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the specific amino acid sequences and structures of monomers will clearly influence the assembly of a pilus and its functions (Vargas et al, 2013; Xiao et al, 2015). Previous researches have suggested that the length of the amino acid sequence and the conformation of G. sulfurreducens pilins leads to a compact assembly mode that may account for the electrical conductivity (Malvankar et al, 2011; Xiao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Before assembly, the subunit was aligned along the pilus axis by the align module of PyMOL to define the initial position and facilitate the searching process. During assembly, the proper distance and ambiguous constraints were set between pairs of amino acids (aromatic amino acids and charged amino acids) from neighboring subunits to narrow the sampling time [8,17]. Furthermore, the pair of residue F1/E5 was also set as a constrained pair.…”
Section: Constructing a Pilus Structure From Subunit Data With Sparsementioning
confidence: 99%
“…The cluster module in Rosetta was then utilized to cluster these models (cutoff radius = 4.0 Å). Since interfacial energy is an approximation of binding energy that represents the stability of the pilin assemblage [8,17], the convergence phenomenon ( Figure 3A-D) and energy scores of the 15 lowest energy models in the biggest cluster for each different range ( Figure 3E-H) could be used to help determine the rotation angle for assembling full atomic models. These results suggested that the models that have a rotation angle of 40 • to 80 • for WT, 90 • to 120 • for A1, 90 • to 120 • for 5A, and 40 • to 80 • for W51W57 had the best convergence phenomenon and the lowest interfacial energy score.…”
Section: Structures Of Wild-type Pilus and Its Mutant Pili For G Sulmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy for modeling pilus structure 17 successfully reconstructed the known structures of the type IVa pili of Neisseria gonorrhoeae 18 ; the type IVb pili of Vibrio cholera 19 20 ; and the T2SS pseudopili of Klebsiella oxytoca 21 from the structure of the pilin monomer, by employing the Rosetta Symmetric Docking protocol 22 with a combination of randomized structural parameters and distance constraints. Here we report that the application of this modeling approach suggests options, different than those derived from homology modeling, for how the G. sulfurreducens pilus assembles to yield the experimentally observed close-packing of aromatic amino acids.…”
mentioning
confidence: 99%